Comparison of Gluteus Medius and Quadratus Lumborum Muscle Activity During Hip Abduction Exercises in Individuals With Gluteus Medius Weakness - Kyung-hee Jung; Il-young Moon; One-bin Lim; Chung-hwi Yi (Physical Therapy Korea)
Background: The purpose of this study was to compare gluteus medius (Gmed) and quadratus lumborum (QL) muscle activities and the Gmed/QL activity ratio, during five hip abduction exercises in individuals with Gmed weakness. Objects: Nineteen participants with clinically identified Gmed weakness performed five hip abduction exercises: side-lying hip abduction (SHA), side-bridge (SB), SB using sling (SB-sling), SB with hip abduction (SB-HA), and SB-HA using sling (SB-HA-sling). Surface electromyography recorded Gmed and QL, normalized to %maximum voluntary isometric contraction (%MVIC). A repeated-measures ANOVA was used to assess differences across conditions. Results: Significant differences were found in Gmed (F = 68.980, p = 0.001) and QL (F = 10.676, p = 0.001) activation across exercises. Gmed activity was highest in SB-HA (61.77 ± 14.46 %MVIC), while SHA produced the highest Gmed/QL activity ratio (1.70 ± 0.26), indicating more selective Gmed activation. SB and SB-sling showed lower Gmed activity and higher QL activation. SB-HA-sling resulted in moderate Gmed activation without significantly increasing QL activation. Conclusion: The SB-HA exercise is effective for co-activating Gmed and QL, while SHA and SB-HA-sling are better suited for selectively targeting Gmed with minimal QL compensation. These findings support exercise selection based on specific rehabilitation goals.